A Stress "Deafness" Effect in European Portuguese. (March 2015) - Correia, Susana; Butler, Joseph; Vigário, Marina; Frota, Sónia
Research on the perception of word stress suggests that speakers of languages with non-predictable or variable stress (e.g., English and Spanish) are more efficient than speakers of languages with fixed stress (e.g., French and Finnish) at distinguishing nonsense words contrasting in stress location. In addition, segmental and suprasegmental cues to word stress may also impact on the ability of speakers to perceive stress. European Portuguese (EP) is a language with variable stress and vowel reduction. Previous studies on EP have identified duration as the main cue for stress. In the present study, we investigated the perception of word stress in EP, both in nuclear (NP) and post-nuclear (PN) positions, by means of three experiments. Experiment 1 was an ABX discrimination task with stress and phoneme contrasts, without vowel reduction. Experiments 2 and 3 were sequence recall tasks with stress and phoneme contrasts, vowel reduction being added to the stress contrast only in experiment 3. Results showed significantly higher error rates in the stress contrast condition than in the phoneme contrast condition, when duration alone (PN), or duration and pitch accents (NP), are present in the stimuli (experiments 1 and 2). When vowel reduction is added, EP speakers are able to perceive stress contrasts (experiment 3). The results show that vowel reduction appears to be the most robust cue for stress in EP. In the absence of vowel quality cues, a stress "deafness" effect may emerge in a language with non-predictable stress that combines both suprasegmental and segmental information to signal word stress. These findings have implications for claims of a prosodic-based cross-linguistic perception of word stress in the absence of vowel quality, and for stress "deafness" as a consequence of a predictable stress grammar.